Acute intermittent porphyria and pregnancy: an obstetric challenge - Meena, Pragati; Jain, Sandhya; Rajaram, Shalini; Gupta, Bindiya; Goel, Neerja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Acute intermittent porphyria is a rare autosomal dominant disease caused by a mutation in the gene coding for the porphobillinogen deaminase enzymes in heam biosynthesis. The disease manifests as acute attacks of neuropsychiatric dysfunction and neurovisceral manifestations presenting as acute abdomen. In pregnancy, 54% patient has exacerbation of attacks in the form of seizures and acute abdomen occurs due to hormonal changes. Prevalence of acute intermittent porphyria is 1-2/200000 in general. Here we report a case of 36 year old women, G4P1L2A2 presenting at 10+4 weeks of gestation requesting pregnancy termination. Patient was diagnosed as case of acute intermittent porphyria with porphyic polyneuropathy 6 months back. At that time her main symptoms were acute pain abdomen with numbness and weakness in all four limbs. Her urinary porphobillinogen and 5 ALA raised. Her CECT of brain and nerve conduction studies were normal. Since then she is on Tablet Gabapentin 300 mg H.S. She underwent successful pregnancy termination by suction and evacuation under spinal anesthesia and she refused for copper-T insertion. Only safe drugs were used for procedure and she was discharged with advice of barrier contraception.